HUMOR DAN KOMEDI DALAM SEBUAH KILAS BALIK SEJARAH - Muhammad Yunus Anis (CMES (Center of Middle Eastern Studies), 2013)
This paper describes the brief history of Humour in Arabs from (1) the earlier preIslamic period, (2) the Islamic period, (3) the medieval Arabic Literature (Abbasid), and (4) Mamaluke, Fatimid, Ayyubid, and Ottoman periods. This paper will try to show thatArabic literature is rife with the unique taste of Arabs in humour and comedy. Finally, the result of data analysis shows that humour in the earlier pre-Islamic period and the Islamic period is used dominantly at satirical poem which is called hija‟. But in the medieval period until Ottoman period, Arabic humour and comedy has been spreading to the modern prose, shuch as romantic novel, elegant style of fable, public theater – shadow play and some of elegiac short stories.